Using machine learning and natural language processing to automatically extract information from software documentation - ÓLAFSDÓTTIR, HELENA (My University, 2019)
Engineers face many challenges when it comes to using and maintaining software documentation. The OD3 is a vision for the future of software documentation which proposes that documentation should be generated based on user queries. There are many steps that need to be taken to create such a system. This research takes one of those necessary steps by investigating the categories of software knowledge that are contained in software documentation, automatically classifying sentences from software documentation into those sentences, and exploring methods to identify sentence relations. This analysis was conducted on one case documentation. A system, Software Documentation Supporter (SDS), was then built to explore and evaluate the results. The aim of the SDS is to support the user when navigating through long software documentation. In the system, the user can choose from a list of questions, and the software knowledge extracted from the documentation is used to answer those questions. The results were evaluated using a quantitative and a qualitative approach. As the sample size of the evaluation was small, the quantitative results did not show a significant difference in the time it took users to solve tasks using the SDS, compared to using only the documentation. The qualitative results showed that participants did feel that the SDS supported them and that it helped them navigate the documentation, however it was also clear that improvements need to be made both in regards to the method, and the design of the system.
Keywords: software; documentation; architecture; requirement; natural language processing; classification; clustering